2017
DOI: 10.1038/s41598-017-12151-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of medroxyprogesterone acetate in women with ovarian endometriosis undergoing controlled ovarian hyperstimulation for in vitro fertilization

Abstract: This study investigated the use of medroxyprogesterone acetate (MPA) or a short protocol for controlled ovarian hyperstimulation (COH) in patients with advanced endometriosis who have normal ovarian function, and to compare cycle characteristics and pregnancy outcomes after frozen-thawed embryo transfer (FET). This was a retrospective case-control study of 244 patients with advanced endometriosis undering COH. The patients were allocated to three groups: the surgery group with MPA COH (62 patients, 71 IVF/ICSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 53 publications
(55 reference statements)
2
18
0
Order By: Relevance
“…Long-acting FSH has also been used in a fashion of random start with antagonist protocol [26], but there is lack of investigation specific to luteal stimulation. As for PPOS without GnRH antagonist, the group in China led by Kuang [8,10,27 Almost all previous relevant studies unanimously required higher dosage of HMG with or without longer duration for stimulation in MPA-PPOS [8,12,33]. In our finding, there was no significant difference in stimulation duration and gonadotrophin consumption between PPOS and antagonist protocol.…”
Section: Resultssupporting
confidence: 43%
“…Long-acting FSH has also been used in a fashion of random start with antagonist protocol [26], but there is lack of investigation specific to luteal stimulation. As for PPOS without GnRH antagonist, the group in China led by Kuang [8,10,27 Almost all previous relevant studies unanimously required higher dosage of HMG with or without longer duration for stimulation in MPA-PPOS [8,12,33]. In our finding, there was no significant difference in stimulation duration and gonadotrophin consumption between PPOS and antagonist protocol.…”
Section: Resultssupporting
confidence: 43%
“…This was a prospective non-inferiority trial. The sample size was estimated according to previous studies (9)(10)(11)(12)16). We assumed that the mean number of oocytes retrieved in the three groups was 10.0 oocytes (18) and the non-infertility margin was 2.0 oocytes.…”
Section: Sample Sizementioning
confidence: 99%
“…Patients with thin endometria during natural or stimulation cycles were recommended to adopt the hormone replacement protocol. A hormone substituted cycle was performed for patients with thin endometria during natural or stimulation cycles which had be previously described (16). The maximum number of transferred embryos was two per patient.…”
Section: Transfer Of Cryopreserved-thawed Embryosmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Prior studies have shown that the PPOS protocol with medroxyprogesterone acetate (MPA) could produce competent oocytes/embryos and achieve comparable pregnancy outcomes to standard GnRH agonist short protocol. 7,10,11 Coupled with the application of frozenthawed embryo transfer (FET) and dual trigger of GnRH agonist with low-dose hCG, the PPOS protocol also allows for nearly complete avoidance of OHSS occurrence. 12 Nevertheless, use of MPA in the PPOS regimen tends to inhibit pituitary in a more profound manner and therefore requires higher doses of hMG than the GnRH agonist short protocol in patients with or without PCOS.…”
Section: Introductionmentioning
confidence: 99%